To the Problem of Transfer of the National Uniqueness of Proverbs, Sayings and Other Units in Literary Translation - Shohista Khatamkulova (Peerian Journals Publishing, 2022)
The article provides a comparative study of the proverbs, parables and phraseological units in the Russian and Deutsch versions of the novel “Navoi” by Oybek.
Keywords: text; language; translation; language alternative